Chitosan microparticles: influence of the gelation process on the release profile and oral bioavailability of albendazole, a class II compound - Piccirilli, Gisela Noemi (2013)
Encapsulation of albendazole, a class II compound, into polymeric microparticles based on chitosan-sodium lauryl sulfate was investigated as a strategy to improve drug dissolution and oral bioavailability. The microparticles were prepared by spray drying technique and further characterized by means of X-ray powder diffractometry, infrared spectroscopy and scanning electron microscopy. The formation of a novel polymeric structure between chitosan and sodium lauryl sulfate, after the internal or external gelation process, was observed by infrared spectroscopy. The efficiency of encapsulation was found to be between 60 and 85% depending on the internal or external gelation process. Almost spherically spray dried microparticles were observed using scanning electron microscopy. In vitro dissolution results indicated that the microparticles prepared by internal gelation released 8% of the drug within 30 min, while the microparticles prepared by external gelation released 67% within 30 min. It was observed that the AUC and Cmax values of ABZ from microparticles were greatly improved, in comparison with the non-encapsulated drug. In conclusion, the release properties and oral bioavailability of albendazole were greatly improved by using spraydried chitosan-sodium lauryl sulphate microparticles.